Molecular characterization of Staphylococcus aureus MRSA in fresh artisan cheeses from the Puerto Escondido market - Gurgua-Gutiérrez, Ixayana; Galicia-Jiménez, Mónica Marcela; Nieto Castañeda, Irma Gisela; López-Garrido, Serafín Jacobo; Rojas-Herrera, Rafael Antonio; Gamboa-Alvarado, José Guadalupe (Ecosistemas y Recursos Agropecuarios, 2025)
The consumption of artisanal fresh cheeses is a common practice due to their importance in the gastronomic culture of Mexico and Oaxaca. However, fresh cheese has been directly associated with the development of food poisoning and represents one of the greatest risks in the transmission of antibiotic-resistant pathogens, mainly due to the presence of Staphylococcus aureus. This research was conducted with the aim of characterizing the composition and genetic diversity of virulence factors and the mecA gene loci of S. aureus in artisanal fresh cheeses sold in the Puerto Escondido market in San Pedro Mixtepec, Oaxaca. 4 ring cheeses and 4 leaf cheeses were purchased from three cheese factories (24 cheeses), subsequently, a simple random sampling was carried out: quartering technique to obtain six composite samples, were purchased from three cheese factories and evaluated through physicochemical and microbiological analyses using multiplex PCR. The physicochemical variables analyzed were NaCl and Ca, with calcium values ranging from 15.14±0.27 to 28.94±0.66, and NaCl values ranging from 4.2% to 6.5%, classifying the cheeses as very salty. The presence of coagulase-positive, methicillin-resistant Staphylococcus aureus (MRSA) with the SCCmec IV staphylococcal chromosomal cassette was confirmed in all samples. The detected genes encode for enterotoxin E and TSST-1, present in all samples and in two of the samples, respectively. It is concluded that there is an ideal microenvironment for the growth of S. aureus and the production of its toxins.
Keywords: Staphylococcal food poisoning; dairy products; food safety; methicillin-resistant Staphylococcus aureus